Penggunaan Teknologi Informasi dan Kinerja Auditor - Allo, Yohanis Tasik; Paranoan, Anthon; Marewa, Yeheschiel Bartin (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2018)
This study aimed to examine the effect of the information technology application on auditors performance in KAP Makassar. This study performed to the public auditor working in KAP. Data collection will be done with the survey taken from KAP in Makassar by 45 respondents through questionnaires and using proportional random sampling. Test of data quality used validity test and reliability test. Prerequisite test analysis using multicolinierity test, heteroscedasticity test, normality test, and test linieritas.Teknik data analysis will use descriptive analysis, simple regression test and multiple regression. The result of this research indicates that the application of information technology which is represented by three independent variables, skill and knowledge, system usage and perceived usefulness, has a positive and significant influence about the auditor?s performance. The findings of this study recommends increased in information technology usage so that the effectiveness and efficiency of the audit process can be improved.